Self-organization of chalcogen-containing cyclic alkynes and alkenes to yield columnar structures - Werz, Daniel B.; Stäb, Tobias; Benisch, Christoph; Rausch, Bernhard J.; Rominger, Frank; Gleiter, Rolf (Organic letters, 2002)
Close contacts between chalcogen atoms in cyclic dienes and diynes are used to create columnar structures in the solid state. Rigid and fairly planar cycles with chalcogen centers are the preconditions for forming those columnar structures.